2018
DOI: 10.1136/bjsports-2016-096874
|View full text |Cite
|
Sign up to set email alerts
|

Programme frequency, type, time and duration do not explain the effects of balance exercise in older adults: a systematic review with a meta-regression analysis

Abstract: Limitations to this study included the variability in design of balance interventions, incomplete reporting of data and statistical heterogeneity. The design of balance exercise programmes provides inadequate explanation of the observed benefits of these interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
1
18
0
2
Order By: Relevance
“…That study was conducted in outpatient facilities, and most participants were community-dwelling older people with dementia who had higher levels of cognitive and physical function and fewer comorbidities than did our population (44). In addition, comparison of our results with those of systematic reviews of the effects of balance interventions that included older participants, nearly all of whom were community dwelling and without dementia, yielded inconclusive findings (3,14,45). The authors of one review concluded, in line with our results, that exercise program modalities inadequately explained the balance effect (45).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…That study was conducted in outpatient facilities, and most participants were community-dwelling older people with dementia who had higher levels of cognitive and physical function and fewer comorbidities than did our population (44). In addition, comparison of our results with those of systematic reviews of the effects of balance interventions that included older participants, nearly all of whom were community dwelling and without dementia, yielded inconclusive findings (3,14,45). The authors of one review concluded, in line with our results, that exercise program modalities inadequately explained the balance effect (45).…”
Section: Discussionmentioning
confidence: 74%
“…In addition, comparison of our results with those of systematic reviews of the effects of balance interventions that included older participants, nearly all of whom were community dwelling and without dementia, yielded inconclusive findings (3,14,45). The authors of one review concluded, in line with our results, that exercise program modalities inadequately explained the balance effect (45). In contrast, a review of balance exercise in healthy older adults identified effective balance training protocol comprising exercise modalities (duration, frequency) (14).…”
Section: Discussionmentioning
confidence: 76%
“…A direct assessment of dynamic balance in gerontology is lacking, as it is indirectly inferred from walking speed [27] and qualitative self-reports [30]. The search and need for a valid and reliable measure of dynamic balance, i.e., an actual loss of balance, is highlighted by the use of an extraordinary array of 133 balance outcomes in 80 studies [35]. The difficulty in identifying a dynamic balance test may be related to the paradox that the number of falls increases despite reductions in walking speed.…”
Section: Discussionmentioning
confidence: 99%
“…Para equilibrar dosis de ejercicio, las recomendaciones dependen de la prescripción de frecuencia de ejercicio, tipo y tiempo. En ausencia de una medida de intensidad, el ejercicio generalmente se prescribe 2-3 veces/ semana durante 45-60 min, con las tareas más difíciles practicadas 2-3 veces/sesión [75], apuntando tanto a la comunidad en general como individual, realizado en un entorno grupal o en el hogar; se aconseja que las personas con alto riesgo (como caídas) no deben estar sin supervisión [76].…”
Section: Ejercicio Para Promover El Envejecimiento Neural Saludableunclassified